2010
DOI: 10.1038/ismej.2010.75
|View full text |Cite
|
Sign up to set email alerts
|

A ‘rare biosphere’ microorganism contributes to sulfate reduction in a peatland

Abstract: Methane emission from peatlands contributes substantially to global warming but is significantly reduced by sulfate reduction, which is fuelled by globally increasing aerial sulfur pollution. However, the biology behind sulfate reduction in terrestrial ecosystems is not well understood and the key players for this process as well as their abundance remained unidentified. Comparative 16S rRNA gene stable isotope probing in the presence and absence of sulfate indicated that a Desulfosporosinus species, which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
244
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(264 citation statements)
references
References 71 publications
(128 reference statements)
13
244
1
1
Order By: Relevance
“…The few abundant taxa account for most of the biomass and carbon cycling, whereas some rare species may be important for the cycling of Biogeography of abundant and rare bacterioplankton L Liu et al certain elements (Pedrós-Alió, 2012). An example from a peatland indicated that rare taxon Desulfosporosinus could contribute most of the sulfate reduction in the peat (Pester et al, 2010). Moreover, abundant and rare bacteria may have different ecological strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The few abundant taxa account for most of the biomass and carbon cycling, whereas some rare species may be important for the cycling of Biogeography of abundant and rare bacterioplankton L Liu et al certain elements (Pedrós-Alió, 2012). An example from a peatland indicated that rare taxon Desulfosporosinus could contribute most of the sulfate reduction in the peat (Pester et al, 2010). Moreover, abundant and rare bacteria may have different ecological strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In this concept initially developed for macroorganisms, keystone species are commonly understood as the 'backbone' of the community on which the stability of the entire system depends (Paine, 1969). Recently, prokaryotes involved in major biogeochemical processes such as sulfates reducers (Pester et al, 2010) or primary degraders of refractory substrates (Ze et al, 2012) have been regarded as keystone species. Our results suggest that members of the MCG lineage might have a keystone role in archaeal sediment communities.…”
Section: Evolutionary Relationships Between Freshwater and Marine Mcgmentioning
confidence: 99%
“…Type Ia MOB related to the ones found in our study have been demonstrated to be responsible for methane consumption in many important methane-emitting habitats such as rice paddies (Bodelier et al, 2000), arctic wetlands (Graef et al, 2011), landfills (Chen et al, 2007), lake sediments (Dumont et al, 2011) and floodplains , which has been ascribed to their specific traits enabling them to be very responsive to the periodic availability of methane and other nutrients (Steenbergh et al, 2010;Bodelier et al, 2012). Recent studies assigning species-specific contributions to important biogeochemical cycles using stable isotopes also indicated a disproportionate role of single rare microbial species to globally important processes (Musat et al, 2008;Pester et al, 2010;Peter et al, 2011), strongly suggesting that the traits of the organisms involved will be fundamental to the variability and dynamics in the biogeos p e c ie s n ic h e s function Figure 7 Graphical representation of the three dimensions involved in BEF relationships. The curve of the speciesfunction relationship will depend on the number of niches present, allowing species to be active and contribute to function.…”
Section: Synthesismentioning
confidence: 99%